The incidence of visible underemployment: Evidence for Trinidad and Tobago - Holger Görg; Eric Strobl (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2001)
This paper presents an empirical analysis of the incidence of visible underemployment in Trinidad and Tobago. Visible underemployment consists of workers who work less than the normal duration of working hours but are willing and available to work more. We find that compared to other groups of the labour force the visibly underemployed tend to be less educated and are more likely to work in the private sector. We also find that their revealed behaviour is consistent with their desire for more hours. Relative to the jobs of the visibly underemployed, full-time jobs would, in addition to providing more hours, be more attractive because of greater employment stability and higher returns to job specific attributes, although the personal characteristics of the visibly underemployed are better rewarded in their own jobs. Only about 50 per cent of the visibly underemployed are able to find full-time employment within three months and little except firm size helps predict who will.
Keywords: 330; Kurzarbeit; Qualifikation; Beschäftigung; Trinidad und Tobago